2018
DOI: 10.3390/sym10020040
|View full text |Cite
|
Sign up to set email alerts
|

Three Classes of Fractional Oscillators

Abstract: This article addresses three classes of fractional oscillators named Class I, II and III. It is known that the solutions to fractional oscillators of Class I type are represented by the Mittag-Leffler functions. However, closed form solutions to fractional oscillators in Classes II and III are unknown. In this article, we present a theory of equivalent systems with respect to three classes of fractional oscillators. In methodology, we first transform fractional oscillators with constant coefficients to be line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 72 publications
0
39
0
1
Order By: Relevance
“…For more information on Mittag-Leffler functions see [35]. Now let us obtain the solution of the following fractional differential equation, whose solution is fundamental for our main results of this paper.…”
Section: Definition 4 ([3334]) the Two-parameters Mittag-leffler Fumentioning
confidence: 99%
“…For more information on Mittag-Leffler functions see [35]. Now let us obtain the solution of the following fractional differential equation, whose solution is fundamental for our main results of this paper.…”
Section: Definition 4 ([3334]) the Two-parameters Mittag-leffler Fumentioning
confidence: 99%
“…Fractional calculus has been made use of to model memory phenomena and hereditary properties [2][3][4][5][6]8]. Its application areas have been widely exploited, such as non-Newtonian flow, damping material [4,[8][9][10], viscoelasticity theory, anomalous diffusion [11][12][13][14], and control theory [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that fractional calculus can describe memory phenomena and hereditary properties of various materials and processes [2][3][4][5][6][7]10]. In recent decades, fractional calculus has been applied to different fields of science and engineering, covering viscoelasticity theory, non-Newtonian flow, damping materials [4,7,11,12], anomalous diffusion [13][14][15][16], control and optimization theory [17][18][19], financial modeling [20,21], and so on.…”
Section: Introductionmentioning
confidence: 99%